SITUATION AND SOME FACTORS RELATED TO PATIENT SAFETY CULTURE AT KIEN GIANG GENERAL HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: Patient safety culture (ATNB) is considered the leading criterion in the treatment andcare of patients at medical facilities.Objective: Describe the situation and analyze some factors related to patient safety culture of healthworkers at Kien Giang general hospital, 2021.Methods: Cross-sectional study, quantitative research.Results: The study collected quantitative information from 950 health workers at Kien Gianggeneral hospital through questionnaires. The research results show that the rate of health workerswho respond positively to the patient safety culture is quite high.Conclusion: The rate of positive response to patient safety culture of health workers is 70.1%. TheFactors related to patient safety culture: Group of health workers who have contact with patients; Thegroup of health workers are nurses and the group of health workers are doctors/pharmacists (p
Keywords: Patient safety culture, Health workers, Related factors.